PENGARUH INSEKTISIDA TERHADAP AKTIVITAS DAN KEMUNCULAN KUMBANG BARU Elaeidobius kamerunicus FAUST (COLEOPTERA: CURCULIONIDAE) PADA BUNGA JANTAN KELAPA SAWIT (Elaeis guineensis Jacq.) - Agus Eko Prasetyo; Agus Susanto (Jurnal Penelitian Kelapa Sawit, 2019)
Elaeidobius kamerunicus is the main pollinating insect in oil palm plantations in Indonesia which influences the oil palm fruit set. Theoil palm (Elaeis guineensis) male inflorescence is the only one of their breeding site. The application of insecticides, especially those directly to the male inflorescence, can affect the activity and breeding of pollinator insects. Various insecticides include Deltamethrin (2 mL/L), Lamda Sihalotrin (2 mL/L), Dimehipo (2 mL/L), Asefat (1.5 g/L), Fipronil (2.5 mL/L), Chlorantraniliprol (1 mL/L), Flubendiamide (0.5 mL/L) and B. Thuringiensis (2 mL/L) have been tested on E. kamerunicus weevils by in vivo trial and on anthesising male inflorescence at different levels of bloom (25 %, 50%, 75% and 100%) in the field. The weevils mortality observations were carried out for 5 days after the insecticides application in the laboratory while observations in the field included the number of weevils visit before and after insecticide application until the end of the male flower anthesis and the number of new emerged weevil in each spikelet after 21 days of incubation. The results showed that the chemical insecticides i.e. Deltametrin, Lamda Sihalotrin, Dimehipo, Asefat, and Fipronil were killed the weevil, affecting the weevil visit on anthesising male inflorescence 1-3 days later, and decreasing the number of new emerged weevil from each spikelet of male inflorescence after incubation for 21 days. Meanwhile, the treatment of Chlorantraniliprole and Flubendiamide and B. thuringiensis did not affect the development of E. kamerunicus both in the laboratory and in the field so that they were safe for oil palm pollinating naturally.